Systematic Literature Review of Hearing Preservation Rates in Cochlear Implantation Associated With Medium- and Longer-Length Flexible Lateral Wall Electrode Arrays - Van de Heyning, Paul H; Dazert, Stefan; Gavilan, Javier; Lassaletta, Luis; Lorens, Artur; Rajan, Gunesh P; Skarzynski, Henryk; Skarzynski, Piotr H; Tavora-Vieira, Dayse; Topsakal, Vedat; Usami, Shin-ichi; Van Rompaey, Vincent; et al. (Frontiers in Surgery, 2022)
Background The last two decades have demonstrated that preoperative functional acoustic hearing (residual hearing) can be preserved during cochlear implant (CI) surgery. However, the relationship between the electrode array length and postoperative hearing preservation (HP) with lateral wall flexible electrode variants is still under debate. Aims/Objectives A systematic literature review to analyse the HP rates of patients with residual hearing for medium length and longer lengths lateral wall electrodes. Method Systematic literature review methodology was applied following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) recommendations to evaluate the HP rates of medium length and longer length lateral wall electrodes from one CI manufacturer (medium length FLEX 24TM, longer length FLEX 28 TM and FLEX SOFT TM, MED-EL, Innsbruck, Austria). A search using the search engine PubMed (https://www.ncbi.nlm.nih.gov/pubmed/) was performed using the search terms “hearing preservation” or “residual hearing” and “cochlear implant” in “All fields”. Articles published only in English between the 1st of January 2009 and the 31st of December 2020 were included in the search. Results The HP rate was similar between medium length (93.4-93.5%) and longer length electrodes (92.1-86.8%) at 4 months (p=0.689) and at 12 months (p=0.219). In the medium electrode length group, patients under the age of 45 years had better HP than patients above the age of 45 years. Conclusions Both medium length and longer length electrode arrays showed high hearing preservation rates. Considering the hearing deterioration over time, implanting a longer length electrode at primary surgery should be considered, thus preventing the need for future reimplantation.